Financial development, foreign direct investment, exchange rate regimes, and economic growth: new evidence from african economies - Grandes, Martin (2023)
This paper examines empirically the extent to which financial development, Foreign Direct Investment (FDI) and exchange rate regime (ERR) altogether positively influence economic growth in Africa. To achieve this, we build two baseline panel data samples of African countries and new expanded datasets spanning 1980-2015 using a small sample adjusted Generalized Method of Moments (GMM) estimator. To check the robustness of our results, we built two other panel samples by adding on the two previous panel data samples, data from emerging and developed countries, and repeating the analysis. The results from the estimations suggest that financial development, FDI influence positively and significantly economic growth, whereas exchange rate regime has no significant effect on economic performance, controlling for the usual growth- regression variables like trade openness, human capital, investment, governance, and the lagged value of per capita GDP.